Language Planning and Policy for Equal Footing and Justice in Federal Nepal - Yadav, Lekhnath (Journal of the Institute of Engineering, 2018)
The present article makes an analysis drawing on research and the available literature of the language planning policy for equal footing and justice in federal Nepal. Language planning in Nepal has been largely dominated by the political scenario of Nepal. Nepal has focused on poverty reduction in all of its national plans and policies since 1990. The discourse of ‘development’ in late capitalism is largely dominated by economic perspective. It invokes the globalization, a free market economy where corporate power addresses the needs of educational and economic policies and planning to address the needs of the global market, rather than focusing on the everyday local needs of people. However, the ideology of development – as – economic – growth disregards social justice and equity. Nepal’s educational policies, largely driven by donors, embracing the global ideology. The ideology of language planning is problematic as the minority is doomed to remain in the verge of getting marginalized. In federal Nepal, English language needs to be taught as a subject, rather than used for the medium of instruction in order to bring each and every rank and file on the equal footing. As such the language planning in Nepal under the federal system should be based on the principle of social justice that ensures equality in educational opportunities. Journal of the Institute of Engineering, 2017, 13(1): 232-238